The impact of globalisation on social work practice in Malaysia - Amin, Samir Muhazzab; Mohammad, Mohd Suhaimi (Human Resource Management Academic Research Society, 2021)
Globalisation has significantly changed the pattern of social work including social development, economies, culture and environment in Malaysia. A measurable definition of globalisation has been described in this paper. The impact of globalisation on the Malaysian social work practice has transformed through the various stages of its development experience over the past decade. With this in mind, this paper is a review in which analysed the existing literature and highlighted the impacts of globalisation especially in Malaysia. The other main findings of the paper are that the globalism effect towards social work can be very diverse in different areas of the world including movement of people, culture, education and economy. There is a need to contextualize change in social work versus a broader political and economic context. Malaysia society has also posed many challenges in balancing needs and benefits with greater engagement with globalisation.